The Prosecution by the Pidie State Prosecutor Against the Criminal Action of Corruption Gampong Income and Shopping Budget - Suhaibah Suhaibah; Armiwal Armiwal; Afdhalul Gunawar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Law Number 6 of 2014 also strengthens the allocation of Village funds (ADD) originating from the Regency/City balancing funds. If previously there were almost no districts/cities that provided ADD at least 10 percent of the balancing fund without any sanctions, then Article 72 of the Village Law gives the government the right to impose sanctions by delaying and even deducting the balancing fund in the amount of the allocation of funds not given to Village. Aim for knowing the prosecution process by the Pidie State Prosecutor's Office against the perpetrators of corruption in the Gampong Revenue and Expenditure Budget (APBG) and obstacles in the prosecution process by the Pidie State Prosecutor's Office. This research is a type of empirical juridical normative research, data collection in research is carried out through library and field research. Literature research by studying books, laws and regulations. Field research by interviewing respondents and informants.The results showed that the prosecution process by the Pidie State Prosecutor's Office against perpetrators of corruption in the Gampong Revenue and Expenditure Budget (APBG). Technically, the receipt of the case is recorded in the register of receipt of case files, and the report is reported using the LP. In the event that the investigation is considered complete, the investigator hands over the responsibility for the suspect and evidence to the public prosecutor. At this stage, the examination of the suspect is intended to avoid making mistakes in persona being prosecuted before the trial. Obstacles in the prosecution process by the Pidie District Attorney against perpetrators of corruption in the Gampong Revenue and Expenditure Budget (APBG).